Diversity of arsenite oxidizing bacterial communities in arsenic-rich deltaic aquifers in West Bengal, India - Ghosh, Devanita; Bhadury, Punyasloke; Routh, Joyanto (Frontiers in Microbiology, 2014)
High arsenic (As) concentration in groundwater has affected human health, particularly in South-East Asia putting millions of people at risk. Biogeochemical cycling of As carried out by different bacterial groups are suggested to control the As fluxes in aquifers. A functional diversity approach in link with As precipitation was adopted to study bacterial community structures and their variation within the As contaminated Bengal Delta Plain (BDP) aquifers of India. Groundwater samples collected from two shallow aquifers in Karimpur II (West Bengal, India), during years 2010 and 2011, were investigated to trace the effects of inter-annual variability in precipitation on community structure and diversity of bacterial assemblages. The study focused on amplification, clone library generation and sequencing of the arsenite oxidase large sub-unit gene aioA and 16S rRNA marker, with respect to changes in elemental concentrations. New set of primers were designed to amplify the aioA gene as a phylogenetic marker to study taxonomically diverse arsenite oxidizing bacterial groups in these aquifers. Overall narrow distribution of bacterial communities based on aioA and 16S rRNA sequences observed was due to poor nutrient status and anoxic conditions in these As contaminated aquifers. Proteobacteria was the dominant phylum detected, within which Acidovorax, Hydrogenophaga, Albidiferax, Bosea and Polymorphum were the major arsenite oxidizing bacterial genera. The structure of bacterial assemblages including those of arsenite oxidizing bacteria were affected by an increase in major elemental concentrations (e.g., As, iron, sulfur, and silica) within two sampling sessions, which was supported by PCA analysis. One of the significant findings of this study is detection of novel lineages of 16S rRNA-like bacterial sequences indicating presence of indigenous bacterial communities across both wells of BDP that can play important role in biogeochemical cycling of elements including As.